Development and validation of an analytical testing method to evaluate the irradiation history of dried chicken meat - Taghvaei, Mostafa (Kansas State University, 2019)
There have been health concerns regarding the consumption of irradiated chicken jerky treats (CJT), and there is a lack of an established method to quantify the irradiation dose to ensure the legal limits. Radiolytic lipid products can be used to back-trace the irradiation history of foods. The formation kinetics of 2-dodecylcyclobutanone (2-DCB) and hydrocarbons were studied in gamma-irradiated (0 to 50 kGy) tripalmitin, chicken fat, and chicken jerky treats (CJT) to assist in method development for dose prediction. Among different methods to extract lipid-based irradiation markers, solid phase micro extraction (SPME) could provide a faster and simpler method to estimate the irradiation history of fat containing food products. The SPME technique was optimized in terms of fiber stationary phase, extraction solvent, time, and temperature to extract 2-DCB and hydrocarbons from irradiated CJTs. The analytes were identified and quantified using Gas Chromatography–Mass Spectrometry (GC-MS) in scan and selected ion modes (SIM). Thirty-nine different hydrocarbons, aldehydes, and ketones were identified, among which 33 increased with irradiation dose. Formation of such radiolytic products occurred along with reduction of all major fatty acids of chicken fat up to 20 kGy. Pentadecane, 1-pentadecene, 1-tetradecene, and 8-heptadecene, which are likely derived from palmitic and oleic acid, were shown the highest concentration and linear regression (formation kinetic of 658531 peak area/kGy, R² = 0.998). Water dilution (1:5) was needed to mobilize 2-DCB and allow partition to the headspace form the CJT matrix. Increasing the incubation temperature up to 80 °C resulted in higher response. Spiking control jerky samples with 2-DCB from 10 to 150 ppb compared with spiking water revealed a significant effect that the food matrix has in lowering the signal obtained from 2-DCB. The concentration of 2-DCB increased linearly (10.8 ppb/kGy, R2 = 0.999) from 0 to 543 ng/g CJT with irradiation from 0 to 50 kGy. Addition of glycerol to the formulation of chicken jerkies did not significantly affect the formation or measurement of 2-DCB. Pentadecane is the major hydrocarbon in irradiated fat and could be used for dose measurement of fat containing irradiated samples showing the highest concentration among hydrocarbons and a linear regression of 0.95. SPME-coupled GC-MS analysis can serve as a suitable technique to quantify 2-DCB and hydrocarbons concentrations in CJT as irradiation markers. A limit of detection of 50 ppt, and a limit of quantitation of 4 ppb was determined for 2-DCB using the optimized parameters of the method. This method provides a fast, simple, and environmentally friendly alternative for the existing solvent extraction methods for analyzing irradiation markers.
Keywords: Chicken jerky treat; Irradiation marker; 2-DCB; GC-MS; SPME